2013
DOI: 10.1111/1750-3841.12280
|View full text |Cite
|
Sign up to set email alerts
|

Suitability of Bifidobacterium spp. and Lactobacillus plantarum as Probiotics Intended for Fruit Juices Containing Citrus Extracts

Abstract: A strain of Lactobacillus plantarum and 4 strains of bifidobacteria were inoculated in apple juice and in a commercial beverage labeled as "red-fruit juice," containing citrus extracts as natural preservatives; the suitability of the probiotics was evaluated in relation to their resistance to 2 kinds of citrus extracts (biocitro and lemon extract), survival in juices at 4 and 37 °C, and inhibition of Zygosaccharomyces bailii. Cell count of L. plantarum and bifidobacteria over time was fitted through the Weibul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Finally it was concluded that L. plantarum preserved its viability for 30 days. In addition, the application of L. plantarum c19 led also to high preservation of viabilities [13]. The same outcome was observed in the case of the application of a novel potential probiotic L. paracasei K5 by Plessas et al [38].…”
Section: Feasibility Of Pomegranate Juice Selection As Potential Subssupporting
confidence: 55%
See 2 more Smart Citations
“…Finally it was concluded that L. plantarum preserved its viability for 30 days. In addition, the application of L. plantarum c19 led also to high preservation of viabilities [13]. The same outcome was observed in the case of the application of a novel potential probiotic L. paracasei K5 by Plessas et al [38].…”
Section: Feasibility Of Pomegranate Juice Selection As Potential Subssupporting
confidence: 55%
“…Dairy-fermented products are considered, nowadays, as optimum carriers of probiotic strains. However, in the last decade, several reasons, such as (i) lactose-intolerance, (ii) allergies after dairy products consumption and (iii) a general emerging food trend towards a vegan diet, have turned research to the production of innovative, alternative mediums for probiotic delivery [12,13]. Regarding this new trend, fruit and vegetables have started to gain the attention from the food industry and consumers.…”
Section: Fruit Juices As Substrates For Probiotic Deliverymentioning
confidence: 99%
See 1 more Smart Citation
“…However, there has been a trend for lower cholesterol, lactose free, dairy free, vegetarian, and vegan friendly options [3,6]. A number of studies have investigated the use of fruit juices as a medium for probiotic growth and viability [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. These studies have demonstrated a potential for probiotics in a variety of different fruit juices such as orange, grape, pomegranate, peach, and apple.…”
Section: Introductionmentioning
confidence: 99%
“…37 Therefore, controlling the acidity of LJ could be an effective way to extend its shelf-life, and improve its quality and marketability. 39,40 For the purpose of maintaining the essential composition and quality factors of the juice, the addition of sugars or acids can be permitted to control acidification of the LJ which was endorsed in the individual standard". 41 In general, the most commonly used methods of controlling acidification of LJ include: adding organic acid, such as citric acid and acetic acid; the use of acid-producing bacteria and blending with acidic fruit juices such as orange, lemon, apple and cranberry juice.…”
Section: Lactobacilli Reduce Inflammation In Shigellosis Mousementioning
confidence: 99%